2018
DOI: 10.1016/j.aprim.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Conductas sexuales de riesgo y actividades preventivas frente al cáncer de cuello uterino en mujeres universitarias vacunadas frente al VPH

Abstract: The prevalence of sexual risk behaviours in non-vaccinated women is elevated, and it is related to the lack of use of barrier contraceptive methods. The vaccination against HPV could affect sexual behaviours and the participation in the CCSP. Therefore, the information received by young people about contraceptive methods, sexually transmitted diseases, and cancer prevention should be reinforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
1
1
3
Order By: Relevance
“…Additionally, a Spanish study showed that the prevalence of sexual risky behaviors was high in non-vaccinated university women and was primarily related to the non condom use. This finding contradicts the idea that vaccinated women could increase their sexual risks because of the protection ascribed to vaccination 17 .…”
Section: Discussioncontrasting
confidence: 67%
“…Additionally, a Spanish study showed that the prevalence of sexual risky behaviors was high in non-vaccinated university women and was primarily related to the non condom use. This finding contradicts the idea that vaccinated women could increase their sexual risks because of the protection ascribed to vaccination 17 .…”
Section: Discussioncontrasting
confidence: 67%
“…However, in Spain, there are no studies on the users’ experience in this context. Previous Spanish studies have focused on cervical cancer screening evaluation [16], the prevalence of precancerous lesions and the types of HPV present in cytological samples [17–19] as well as HPV vaccination [20–24].…”
Section: Introductionmentioning
confidence: 99%
“…Esta epidemia invita a la reflexión respecto de las acciones sanitarias que se han implementado, surgiendo la necesidad de establecer diagnósticos situacionales enfocados en los grupos etarios más afectados, con la finalidad de lograr la promoción efectiva de medidas de autocuidado enfocadas en la prevención de la infección. Es de recordar que según Orem 7 , el autocuidado es una actividad aprendida y que depende del grado de maduración de los individuos, es por ello que resulta importante identificar los factores que puedan incidir en el desarrollo del mismo, entre los cuales se encuentran las actitudes y las conductas, aspectos que han sido identificados como potenciadores del déficit del autocuidado con relación a las infecciones de transmisión sexual [8][9][10][11][12][13] .…”
Section: Introductionunclassified